2015
DOI: 10.1002/gea.21507
|View full text |Cite
|
Sign up to set email alerts
|

Geoarchaeological Investigations in Mesoamerica Move into the 21st Century: A Review

Abstract: Over the past thirty years, geoarchaeology has moved from the fringe to mainstream status within Mesoamerican archaeological investigations. This review focuses on works published since the year 2000. Five themes are identified as central to recent studies: (1) the correlation of environmental change and cultural history; (2) anthropogenic environmental impacts; (3) ancient land cover, land use, and diet; (4) archaeological prospection; and (5) provenance studies. These themes are often interwoven in the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 261 publications
(307 reference statements)
0
16
0
Order By: Relevance
“…The variability in mobility and social organization under which ceramic technology is first developed needs to be understood on a regional basis. Ceramic sourcing (e.g., Bong, Matsumura, Yokoyama, & Nakai, ; Dunning et al., ; Eerkens, Neff, & Glascock, ; Gonzales, Arakawa, & Koenig, ; Mange & Bezeczky, ; Pavia, Marsaglia, & Fitzpatrick, ; Šegvić et al., ) is one effective way of assessing the nature of the adoption of pottery through the identification of production zones, the intensity of production, and the extent of circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in mobility and social organization under which ceramic technology is first developed needs to be understood on a regional basis. Ceramic sourcing (e.g., Bong, Matsumura, Yokoyama, & Nakai, ; Dunning et al., ; Eerkens, Neff, & Glascock, ; Gonzales, Arakawa, & Koenig, ; Mange & Bezeczky, ; Pavia, Marsaglia, & Fitzpatrick, ; Šegvić et al., ) is one effective way of assessing the nature of the adoption of pottery through the identification of production zones, the intensity of production, and the extent of circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that some bajos that today contain seasonal swamps (with standing water only in the rainy season) were home to shallow lakes or perennial wetlands as late as the end of the Late Preclassic period (ca. Many bajos appear to have never contained lakes yet remained the focus of ancient Maya settlement into the Late Classic period suggesting that these locations presented the Maya with economic opportunities, probably including agriculture (e.g., Culbert et al, 1996;Dunning et al, 2015a). However, we have also learned that the environmental history of each bajo is unique and needs to be investigated individually if meaningful correlations are to be made with local and regional settlement history (Dunning, Beach, & Luzzadder-Beach, 2006).…”
Section: The Bajo Conundrum and Ancient Maya Canal Researchmentioning
confidence: 99%
“…These canals are all linked to perennial rivers or within perennially moist wetlands near these rivers (Siemens, 1978(Siemens, , 1982. While it is clear that some wetlands were cultivated and gave the Maya an alternative to upland dry farming, wetland farming was only an option in some areas-and likely only at some time periods in those areas (Beach et al, 2008(Beach et al, , 2015bDunning et al, 2015a). Debate hinges on the degree to which various wetlands were suitable for modification and cultivation, the degree to which natural processes may produce features that appear as human-made, and the length and timing of use of various wetland field systems.…”
Section: The Bajo Conundrum and Ancient Maya Canal Researchmentioning
confidence: 99%
“…; Dunning et al. ; Gibson and Venkateswar ; Young ). New areas of research have come out of this effort.…”
Section: Reexamination and Reframingmentioning
confidence: 99%